2012
DOI: 10.5539/jas.v4n8p11
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Nitrate Uptake Efficiency in Young Potted Citrus Trees

Abstract: Fertilizer isotope labelling ( 15 N) of young Lane Late potted orange trees with differential N rates at three phenological periods (end of flowering, fruit set and fruit growth) was used to determine patterns of N uptake response and N efficiency (NUE) along the growing cycle. In a first experiment trees were fed with a saturating N solution in order to determine seasonal variations in N requirements. The second experiment tested four N rates which were equal to (N 1 ), two (N 2 ), three (N 3 ) and four-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…The explanation lies in the highest effectiveness of the root system from citrus in taking up the Fe applied in summer in comparison to spring due to two reasons: the higher soil temperatures in summer, which enhances ion uptake [ 43 ], and the greater development of fine roots and canopy in the period between the end of fruit drop and fruit maturity ( Table 1 ). Data are in line with other studies on N in citrus that found increased N uptake during the summer months [ 10 , 23 , 37 , 44 , 45 , 46 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The explanation lies in the highest effectiveness of the root system from citrus in taking up the Fe applied in summer in comparison to spring due to two reasons: the higher soil temperatures in summer, which enhances ion uptake [ 43 ], and the greater development of fine roots and canopy in the period between the end of fruit drop and fruit maturity ( Table 1 ). Data are in line with other studies on N in citrus that found increased N uptake during the summer months [ 10 , 23 , 37 , 44 , 45 , 46 ].…”
Section: Resultssupporting
confidence: 92%
“…The differences in the enrichment of the various plant organs are consistent with the results obtained in other studies on 57 Fe in citrus and other crops [13,28,30,36] or with other stable isotopes such as 15 N or 44 Ca also in young citrus plants [10,17,26,37,38] and adult plants [20,22,39,40]. In apple, treatment with stable isotope 44 Ca quantified calcium partitioning even at cell level and resulted in significant enrichment in the cell wall of the pericarp through new cross-bridges of Ca-pectates, thereby enhancing fruit strength and delaying fruit degradation and bitter pit development [41,42].…”
Section: Maysupporting
confidence: 90%
See 1 more Smart Citation
“…External N availability and fertilizer application timing greatly affect the size of N reserves. N supplied in the early phenological stage is absorbed at a high rate and mainly allocated to vegetative and/or fruit growth [19][20][21]. By contrast, postponing N supply to later stages is preferentially allocated to storage organs; therefore, this effectively increases the size of winter reserves, although the total N uptake is often reduced due to decreasing growth demand [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Climatic conditions in citrus production zones and traditional cultivation methods favour nitrification of ammonium and, consequently, nitrate-N loss by leaching (Bergström & Brink, 1986). Research conducted in the last years has led to a significant increase in knowledge for improving citrus trees nutrient efficiency where NUE is influenced by N rate (Feigenbaum et al, 1987;Lea-Cox & Syvertsen, 1996;Lea-Cox et al, 2001;Syvertsen & Smith 1996), timing of application (Kubota et al, 1976a & b;Kato & Kubota, 1982;Martínez-Alcántara et al, 2012a;Quiñones et al, 2003Quiñones et al, , 2012, water management (Alva et al, 1998Quiñones et al, 2007), the form of N applied (Cantarella et al, 2003;Mattos et al, 2003), fertilizer splitting (Alva et al, 1998;Morgan et al, 2009;Quiñones et al, 2003), soil type (Martínez et al, 2002;Quiñones et al, 2012) and tree phenological growth stage (Martínez-Alcántara et al, 2012b). A greater synchrony between crop demand and nutrient supply becomes a key factor in NUE improvement.…”
Section: Introductionmentioning
confidence: 99%